Corrosión: inexorabilidad vs. durabilidad - Diaz Tang, Isabel (2016)
In general, a material will tend to corrode in a specific environment when the corrosion products are more stable than the starting material or, when exposed to certain conditions, a corrosion process results favored. In general practice, the goal is to extend the service life of structures, equipment or devices, that is, to improve their durability.